2007
DOI: 10.1038/sj.cdd.4402278
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 is involved in the signal transduction of myelin-associated glycoprotein

Abstract: Myelin-associated glycoprotein (MAG) is a well-characterized axon growth inhibitor in the adult vertebrate nervous system. Several signals that play roles in inhibiting axon growth have been identified. Here, we report that soluble MAG induces activation of Rap1 in postnatal cerebellar granule neurons (CGNs) and dorsal root ganglion (DRG) neurons. The p75 receptor associates with activated Rap1 and is internalized in response to MAG. After MAG is applied to the distal axons of the sciatic nerves, the activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…5B ), suggesting that proBDNF/p75 NTR signaling reduces spine density of hippocampal neurons. It was reported that the transport of the signaling complex that contains the p75 NTR receptor and activated Rap1 plays a role in the effect of myelin-associated glycoprotein (MAG), which is a well-characterized axon growth inhibitor [ 45 ]. During LTD, Rap mediates the NMDA-R-dependent removal of synaptic AMPA receptors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…5B ), suggesting that proBDNF/p75 NTR signaling reduces spine density of hippocampal neurons. It was reported that the transport of the signaling complex that contains the p75 NTR receptor and activated Rap1 plays a role in the effect of myelin-associated glycoprotein (MAG), which is a well-characterized axon growth inhibitor [ 45 ]. During LTD, Rap mediates the NMDA-R-dependent removal of synaptic AMPA receptors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated Rap induces downstream signaling, including the activation of PKC (Wang et al, 2007;Oestreich et al, 2009). Finally, Rap1 activation has been implicated in the modulation of nociceptor functioning (Delcroix et al, 2003;Taniguchi et al, 2008). Western blot analysis of isolated DRG neurons of WT and GRK2 ϩ/Ϫ neurons showed that Rap1 is expressed and that expression levels are similar between WT and GRK2 ϩ/Ϫ neurons (Fig.…”
Section: Grk2 Modulates Rap1 Activation Via Epacmentioning
confidence: 92%
“…In contrast, other proteins typically require geranylgeranylation. The characteristic example is the ras‐like protein 1 (RAP‐1), which after geranylgeranylation activates endocytosis and cell differentiation (Coxon et al ., 2005; Taniguchi et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%